Dom za vešanje - Kusturica, Emir (Italy ; Yugoslavia ; United Kingdom : Forum Sarajevo, 1988)
In this luminous tale set in the area around Sarajevo and in Italy, Perhan, an engaging young Romany (gypsy) with telekinetic powers, is seduced by the quick-cash world of petty crime, which threatens to destroy him and those he loves.
Romology Film Collection
Keywords: Fiction films